Choroidal thickness predicts progression of myopic maculopathy in high myopes: a 2-year longitudinal study. Issue 12 (24th September 2020) - Li, Zhixi; Wang, Wei; Liu, Ran; Wang, Decai; Zhang, Jian; Xiao, Ou; Guo, Xinxing; Jong, Monica; Sankaridurg, Padmaja; Ohno-Matsui, Kyoko; He, Mingguang
Abstract : Aim: To prospectively determine the impact of choroidal thickness (CT) on the myopic maculopathy progression. Methods: This is a prospective, longitudinal, observational study. In total, 434 participants aged 7–70 years with bilateral high myopia (≤-6 D spherical error, range, −6 to −27.0 D) completed follow-up visits for 2 years. The baseline CT centred on the fovea was measured using a swept-source optical coherence tomography (OCT). Myopic maculopathy progression was determined by fundus photography. Logistic model was used to examine the impact of CT at baseline on the myopic maculopathy progression. Likelihood ratio test was adopted for model comparison. Results: The mean baseline age, spherical equivalence and subfoveal CT (SFCT) of the participants were 23.2±12.5 years, −10.50±3.18 D and 153.20±72.76 μm, respectively. Over 2-year's follow-up, 74 of 434 eyes (17.1%) had myopic maculopathy progression. Baseline SFCT was thinner in eyes with myopic maculopathy progression than those without (67.26±37.67 μm vs 170.95±65.45 μm; mean difference, 99.31 μm; 95% CI 83.61 to 115.01 μm; p<0.001). The same patterns of differences were observed in 7–18 years, 19–39 years and 40–70 years. In multivariate logistic regression model, SFCT was a significant risk factor (adjusted OR=0.97, p<0.005) when age, gender, axial length and baseline myopic maculopathy category were adjusted for. The addition of SFCT significantly improved the predictive discrimination of myopic maculopathy progression in comparison with that included established risk factors alone (area under the receiver operating characteristic curve, 0.899 vs 0.942, p<0.001). Conclusion: CT is an independent predictor for myopic maculopathy progression.